Intenziteta jezika v slovenščini in nekaterih drugih južnoslovanskih jezikih - Mikolič, Vesna (Slavistična revija, 2025)
The paper focuses on modality and language intensity in some South Slavic languages (Slovene, Bosnian, Croatian, Serbian and Montenegrin). Based on a corpus-linguistic approach, the study draws on the theoretical frameworks of pragmatics and intercultural pragmatics. Using web text corpora in the aforementioned languages, collected within the CLARIN Knowledge Centre for South Slavic Languages (CLASSLA), a comparative linguistic analysis was conducted to identify linguistic means and communicative patterns associated with language intensity. The comparative study revealed that intensifiers are used more frequently and mitigators less frequently in BCSM languages than in Slovene, indicating a higher level of intensity in online texts in these languages. Despite the lower overall use of intensifiers in Slovene, their frequency in advertising and opinion-based texts suggests that high language intensity is also characteristic of Slovene online communication.
Keywords: corpus-based approach; intensifier; intenziteta jezika; intercultural pragmatics; južnoslovanski jeziki; korpusni pristop; krepilec; medkulturna pragmatika; mitigator; modality; naklonskost; pragmatics; pragmatično jezikoslovje; Slovene language; slovenščina; South Slavic languages; šibilec